2016
DOI: 10.1038/srep35572
|View full text |Cite
|
Sign up to set email alerts
|

Regional-specific effect of fluoxetine on rapidly dividing progenitors along the dorsoventral axis of the hippocampus

Abstract: Hippocampus-dependent cognitive and emotional function appears to be regionally dissociated along the dorsoventral (DV) axis of the hippocampus. Recent observations that adult hippocampal neurogenesis plays a critical role in both cognition and emotion raised an interesting question whether adult neurogenesis within specific subregions of the hippocampus contributes to these distinct functions. We examined the regional-specific and cell type-specific effects of fluoxetine, which requires adult hippocampal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…However, long term regulation of gene expression and epigenetic mechanisms are likely to occur after chronic administration. In this regard, it is important to mention that different classes of antidepressant drugs have been demonstrated to have a plethora of effects in CNS disorders and are also known to have a role in neurogenesis ( Wang et al, 2011 ; Masuda et al, 2012 ; Meneghini et al, 2014 ; Zhou et al, 2016 ; King et al, 2017 ). Many of these effects are sex-dependent ( Gray and Hughes, 2015 ; Kokras and Dalla, 2017 ) and fluoxetine itself is known to induce sex specific effects on neurogenesis ( Hodes et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, long term regulation of gene expression and epigenetic mechanisms are likely to occur after chronic administration. In this regard, it is important to mention that different classes of antidepressant drugs have been demonstrated to have a plethora of effects in CNS disorders and are also known to have a role in neurogenesis ( Wang et al, 2011 ; Masuda et al, 2012 ; Meneghini et al, 2014 ; Zhou et al, 2016 ; King et al, 2017 ). Many of these effects are sex-dependent ( Gray and Hughes, 2015 ; Kokras and Dalla, 2017 ) and fluoxetine itself is known to induce sex specific effects on neurogenesis ( Hodes et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…FLX effect in increasing neurogenesis is well grounded in the literature [87][88][89] . Interestingly, one study that measured neurogenesis based on specific cell types showed that FLX effects depend on the dorsoventral axis of the hippocampus 27 . However, in the present study we used a general neurogenesis marker and found a similar effect of FLX in dHIP and vHIP neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Unmedicated depressed adults presented less granule neurons in the anterior dentate gyrus (DG) when compared to healthy controls 24 , which agrees with reduced hippocampal volume findings observed in patients with major depression 25 . Accordingly, neurogenesis has been proposed by several independent researchers as one of the mechanisms for the antidepressant effect of fluoxetine 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampal CA1 and DG densely expresses 5‐HT 1A receptor . In the DG, 5‐HT 1A receptor majorly expresses on dentate granular cells . Both transgenic and pharmacological evidences showed that 5‐HT1A receptor on dentate granular cells is engaged for depression and anxiety pathology, and antidepressant response .…”
Section: Discussionmentioning
confidence: 99%
“…35 In the DG, 5-HT 1A receptor majorly expresses on dentate granular cells. 35,36 Both transgenic and pharmacological evidences showed that 5-HT1A receptor on dentate granular cells is engaged for depression and anxiety pathology, and antidepressant response. 29,33,37 However, the molecular mechanism responsible for the key pathophysiological process, the dysfunction of 5-HT 1A receptor on dentate granular cells, remains obscure.…”
Section: Discussionmentioning
confidence: 99%